THE EFFECT OF FINANCIAL PERFORMANCE ON COMPANY VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE IN THE COMPANY FOOD AND BEVERAGE COMPANIES LISTED ON THE IDX IN 2020 – 2024 - Melani Tanjung; Abdillah Arif Nasution; Keulana Erwin (CV. Radja Publika, 2025)
This study aims to analyze the effect of financial performance on firm value with Good Corporate Governance (GCG) as a moderating variable. Financial performance is measured using Return on Assets (ROA) and Return on Equity (ROE), while firm value is measured through Price to Book Value (PBV). GCG in this study is proxied by two main indicators, namely managerial ownership and institutional ownership. The objects of the study are food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Data were obtained from annual financial reports officially published through the website [www.idx.co.id]( http://www.idx.co.id ). This study uses a quantitative method with an explanatory approach. The sample was selected using a purposive sampling technique which resulted in 16 companies as samples, with a total of 80 annual observations. Data analysis was conducted using panel data regression and Moderated Regression Analysis (MRA) using EViews 12 software. Classical assumption tests were conducted to ensure model validity, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. The results showed that ROA had a significant positive effect on firm value, while ROE had no significant effect. The findings also showed that managerial ownership moderated the relationship between ROE and firm value, but not ROA. Conversely, institutional ownership was shown to moderate the relationship between ROA and firm value, but not ROE. These results emphasize the importance of GCG in strengthening the effectiveness of financial performance towards creating corporate value. Therefore, companies need to improve strategic ownership structures as part of good governance practices. This research provides practical implications for investors, management, and stakeholders in optimizing corporate value sustainably.